2023
DOI: 10.1371/journal.pone.0281498
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison between single and serial computed tomography images in classification of acute appendicitis, acute right-sided diverticulitis, and normal appendix using EfficientNet

Abstract: This study aimed to develop a convolutional neural network (CNN) using the EfficientNet algorithm for the automated classification of acute appendicitis, acute diverticulitis, and normal appendix and to evaluate its diagnostic performance. We retrospectively enrolled 715 patients who underwent contrast-enhanced abdominopelvic computed tomography (CT). Of these, 246 patients had acute appendicitis, 254 had acute diverticulitis, and 215 had normal appendix. Training, validation, and test data were obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Study limited to specific algorithms and parameters 3. Impact of using all clinical signs not explored Forsstrom et al [ 22 ], 1995 (Finland) CRP, WBC, Phospholipase A2 (PLA2) Used single-layer perceptron and CNN (BP network with 1 hidden layer) models. Each network and dataset were tested 3 times with random weights, learning factor 0.02, momentum 0.7, and 10,000 iterations DiagaiD model: AUC: 0.6825, MSE: 0.0728 LR model: AUC: 0.677, SEM: 0.071 BP model (original data): 2 hidden nodes: (AUC: 0.6363 MSE: 0.0813, 3 hidden nodes: (AUC: 0.5537 MSE: 0.0819) 4 hidden nodes: (AUC: 0.6469 MSE: 0.0747) BP model (transformed data): 2 hidden nodes: (AUC: 0.6219 MSE: 0.0763), 3 hidden nodes: (AUC: 0.6069, MSE: 0.0756) 4 hidden nodes: (AUC: 0.6075, MSE: 0.0732) NR 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study limited to specific algorithms and parameters 3. Impact of using all clinical signs not explored Forsstrom et al [ 22 ], 1995 (Finland) CRP, WBC, Phospholipase A2 (PLA2) Used single-layer perceptron and CNN (BP network with 1 hidden layer) models. Each network and dataset were tested 3 times with random weights, learning factor 0.02, momentum 0.7, and 10,000 iterations DiagaiD model: AUC: 0.6825, MSE: 0.0728 LR model: AUC: 0.677, SEM: 0.071 BP model (original data): 2 hidden nodes: (AUC: 0.6363 MSE: 0.0813, 3 hidden nodes: (AUC: 0.5537 MSE: 0.0819) 4 hidden nodes: (AUC: 0.6469 MSE: 0.0747) BP model (transformed data): 2 hidden nodes: (AUC: 0.6219 MSE: 0.0763), 3 hidden nodes: (AUC: 0.6069, MSE: 0.0756) 4 hidden nodes: (AUC: 0.6075, MSE: 0.0732) NR 1.…”
Section: Resultsmentioning
confidence: 99%
“…A majority of the studies predominantly utilized the incorporation of demographic factors, clinical indicators, and laboratory measurements as the primary features for model training [ 21 , 24 , 26 , 34 , 35 , 37 , 39 , 42 , 44 ]. Radiological assessments, particularly CT images, were the chosen input modality in three studies [ 12 , 20 , 22 ]. Laboratory data served as the exclusive input for four studies [ 19 , 23 , 32 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, some researchers studied appendicitis on CT images using deep learning and radiomics methods 10 15 . Park et al 12 examined patients who underwent abdominal-pelvic CT scans due to acute abdomen and used 3D CNN to classify the appendix region.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the aforementioned studies was to differentiate between appendicitis and normal tissue. Lee et al 13 utilized a CNN to distinguish between appendicitis and diverticulitis, while Park et al 15 applied a CNN to differentiate between appendicitis, diverticulitis, and normal tissue. These studies all suggested the potential application of deep learning methods in evaluating acute appendicitis in different scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation